Epidemiology and Impact of Hand and Wrist Injuries in Major and Minor League Baseball. (July 2021) - Rhee, Peter Charles; Camp, Christopher L.; D'Angelo, John; Desai, Vishal S.; Shin, Steven S.; Sheridan, Donald; Conte, Stan
Background: Professional baseball players are at risk of acute and chronic injuries to their upper extremities.Methods: Major League Baseball's Health and Injury Tracking System, a prospective injury surveillance system, was used to identify and characterize all hand and wrist injuries sustained by all Major League Baseball (MLB) and Minor League Baseball (MiLB) players during the pre-, regular, and postseason throughout 2011-2016. Injuries were included if they resulted in at least 1 day out of play and were sustained during standard baseball activities. Days missed were defined as the time between injury and the first time in which a player was cleared to return to play.Results: During the study period, there were 4478 hand and 1748 wrist injuries throughout MLB and MiLB, which resulted in a total of 105 246 days out of play. This was equivalent to the length of 575 individual MLB player seasons, and the mean days missed per injury was 17 days. Most injuries were traumatic in nature, with 43% (n = 2672) of players injured after being hit by a baseball that mainly occurred during batting (n = 2521; 40%). Injuries that most frequently required surgical intervention were hook of hamate fractures (72%) and scaphoid fractures (60%).Conclusions: Understanding the epidemiology and impact of hand and wrist injuries in MLB and MiLB players may lead to improved management of these injuries and reduce time away from play. Most importantly, preventive measures and/or enhanced protective gear may be developed to minimize these types of injuries in MLB and MiLB.